GENERAL CLASSES OF MUTUALLY INVERSE POLYNOMIALS OF PARTITION - Заторський, Роман Андрійович; Стефлюк, Світлана Дмитрівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper is devoted to the study of general class of mutually inverse polynomials of partitions.